Climate warming induced a stretch of the breeding season and an increase of second clutches in a passerine breeding at its altitudinal limits. Issue 1 (26th March 2021) - Mingozzi, Toni; Storino, Pierpaolo; Venuto, Giampalmo; Massolo, Alessandro; Tavecchia, Giacomo
Abstract: The increase in the average air temperature due to global warming has produced an early onset of the reproduction in many migratory birds of the Paleartic region. According to the "mismatch hypothesis" this response can lead to a decrease in the breeding output when the conditions that trigger the departure from the wintering areas do not match the availability of food resources in the breeding ground. We used 653 brooding events registered during the period 1991–2013 to investigate the link between climatic variables and individual breeding performance of a partially migratory passerine, the Rock Sparrow Petronia petronia, breeding at the altitude limit of its distribution. The laying date (LD) of the earliest first clutch was associated with local spring (minimum) temperatures but did not show a significant trend during the period considered. The LD of the latest first clutch had a positive and statistically significant trend, unrelated to local covariates and resulting in a longer breeding season (∼1.5 days/year). A longer breeding season allowed birds to produce more second clutches, which proportion increased from 0.14 to 0.25. The average breeding success was also positively correlated with the average temperature in July and with the duration of the breeding season. Contrary to expectations, the most important climate-dependent effect was a stretch of the breeding season due to a significant increase of the LD of the latest first-clutches rather than an earlier breeding onset. We show how climate changes act on bird populations through multiple paths and stress the need to assess the link between climatic variables and several aspects of the breeding cycle.